Electrical and Electronics Global Supply Chain: The Significance Effect of Psychological Empowerment on Organizational Business Performance - Loke Wei Kit; Noor Hidayah Binti Abu; Foo-Wah Lim (International Journal of Supply Chain Management, 2018)
Human resources are the most important resources for all types of organizations. Psychological empowerment refers to individuals beliefs in their ability to feel empowered in an organization for better organizational business performance. Although Electrical and Electronics (EE) industry contributes an excellent business performance in the past two decades, this industry was now facing significant challenges in maintaining the growth of their business performance, and it is necessary for them to move up the value chain. Thus, this study aims to examine the relationship between psychological empowerment and organizational business performance of EE industry in Malaysia. In this study, psychological empowerment consists four elements namely autonomy, self-efficacy, impact, and meaning. By using self-administered survey, the data were obtained from 287 respondents from EE companies in Malaysia. The data were then analyzed utilizing Partial Least Square Structural Equation Modelling (PLS-SEM) technique. The findings of this study provide insight into the importance of psychological empowerment in organizational business performance. The findings indicate that, of all those four elements of psychological empowerment, only autonomy, self-efficacy, and meaning have significant influences on the business performance in the EE industry. Lastly, this study will contribute in term of theoretical, managerial and methodological perspectives, limitations and recommendation for future studies.